2022
DOI: 10.1002/jbm4.10622
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion of Menin in Mouse Mesenchymal Stem Cells: An Experimental and Computational Analysis

Abstract: Loss-of-function mutations in the MEN1 tumor-suppressor gene cause the multiple endocrine neoplasia type 1 syndrome. Menin, the MEN1 gene product, is expressed in many tissues, including bone, where its function remains elusive. We conditionally inactivated menin in mesenchymal stem cells (MSCs) using paired-related homeobox 1 (Prx1)-Cre and compared resultant skeletal phenotypes of Prx1-Cre;Men1 f/f menin-knockout mice (KO) and wild-type controls using in vivo and in vitro experimental approaches and mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…The results of this study indicated that the early deletion of menin in the osteoblast lineage affects their late-stage differentiation and matrix mineralization in vitro. Overall, these results confirmed that the use of a biomimetic 3D collagenous matrix may provide better insights into the cell-mediated mineral deposition processes compared to those of 2D systems [ 19 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The results of this study indicated that the early deletion of menin in the osteoblast lineage affects their late-stage differentiation and matrix mineralization in vitro. Overall, these results confirmed that the use of a biomimetic 3D collagenous matrix may provide better insights into the cell-mediated mineral deposition processes compared to those of 2D systems [ 19 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 67%
“…In vivo studies have shown that in mature osteoblasts menin is required to maintain bone mass by affecting bone formation and osteoblast function [ 19 ]. When expressed at early stages of osteoblast differentiation, menin has also been shown to maintain bone mass by regulating osteoclastogenesis and bone resorption in vivo [ 34 ].…”
Section: Discussionmentioning
confidence: 99%